NICHIFOR CRAINIC’S EUCHARISTIC VIEW REFLECTED IN HIS POETIC AND PHILOSOPHICAL WORK - Casvean, Emanuel; Morariu, Iuliu-Marius (European Scientific Journal, ESJ, 2015)
This research is based on Nichifor Crainic’s poetry and philosophy and reflects his view upon the central element of Christian Theology, the theosis, and on the role of the Eucharist in the epectasis. The authors analyse a series of poetic texts with Christian value – such as Cântecul potirului [Song of the Chalice], as well as mystic ones, most of which were written during Nichifor Crainic’s activity as a teacher of mysticism, but also philosophical extracts, part of his more extensive compositions or articles published in magazines such as Gândirea, which was founded by him. Having these extracts as a starting point, the authors illustrated Nichifor Crainic’s philosophical language, extremely profound, yet clear and concise in revealing fundamental Christian truths, of an apodictic importance to the Eastern Christianity and spirituality. As one can observe, the Eucharist is at the core of these beliefs, as it represents the sacrament by which Christ offers Himself as bread and wine, while Christians receive the communion. Given its importance, it comes as no surprise that the philosopher allotted great attention to this act in his works (although he does not offer this subject very much space in his writings). In point of fact, the excerpts which make up the philosopher’s aforementioned mysticism course – and which will be used in their printed form, supervised by archdeacon Dr. Ioan Ică jr., as well as in a new form, typed by several of the philosopher’s students who assisted to some of his lectures – are centred around the Eucharist, presented in its Christological context, thus valuing both its sacramental dimension and its soteriological role in the life of a Christian. It is also interesting to analyse the manner in which Nichifor Crainic links the notion of Eucharist with that of martyrdom in the poem Cântecul potirului [Song of the Chalice]. Here, the author makes a connection between the theology of beauty, the assumption of martyrdom and the intense experience of the mystic ideals of Orthodoxy. Thus, considering the importance of Nichifor Crainic’s view of the Eucharist and its reflection in his poetic and philosophical creation, we believe it is important to have an exegetic approach to this segment of his work. We also have faith that such an undertaking would encourage further research on this subject, standing as a useful tool to those who may take interest in the personality and activity of the reputable philosopher. Naturally, those who wish to analyse our research and extend on it are encouraged to resort to a rich specialized literature, be it Romanian or foreign, even if it touches only tangentially on the subject. This could consist of the philosopher’s works or of related exegesis papers, from a Romanian or Western context. The use of appropriate methodological instruments represents a great asset.